The cost of healthcare for children with mental health difficulties. (September 2013) - Lucas, Nina; Bayer, Jordana K; Gold, Lisa; Mensah, Fiona K; Canterford, Louise; Wake, Melissa; Westrupp, Elizabeth M; Nicholson, Jan M
Objective: Childhood mental health difficulties affect one in every seven children in Australia, posing a potential financial burden to society. This paper reports on the early lifetime individual and population non-hospital healthcare costs to the Australian Federal Government for children experiencing mental health difficulties. It also reports on the use and cost of particular categories of service use, including the Medicare Benefits Schedule (MBS) mental health items introduced in 2006. Method: Data from the Longitudinal Study of Australian Children (LSAC) were used to calculate total Medicare costs (government subsidised healthcare attendances and prescription medications) from birth to the 8th birthday associated with childhood mental health difficulties measured to 8–9 years of age. Results: Costs were higher among children with mental health difficulties than those without difficulties. While individual costs increased with the persistence of difficulties, population-level costs were highest for those with transient mental health difficulties. Although attenuated, these patterns persisted after child, parent and family characteristics were taken into account. Use of the MBS-reimbursed mental health services among children with a mental health difficulty was very low (around 2%). Conclusions: Australian healthcare costs for young children with mental health difficulties are substantial and provide further justification for early intervention and prevention. The current provision of Medicare-rebated mental health services does not appear to be reaching young children with mental health difficulties.